1992
DOI: 10.1111/j.1439-037x.1992.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Spring Barley Responses to Nitrogen Fertilizer and Ethephon in Regions with a Short Crop Growing Season

Abstract: Aspects of intensive management practices such as high N fertilization inputs and plant growth regulator use could potentially increase cereal yields in regions with a short crop‐growing season and occasionally dry and hot weather. A field experiment was carried out for four years (1987 to 1990) at Agronomy Research Centre of McGill University, Canada to evaluate the response of spring barley (Hordeum vulgare L.) cv. Cadette, Laurier and Leger to N rates (0, 70 and 140 kg N ha−1) and ethephon (2‐chloroethyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…In Canada, characterized by more continental conditions, are reported positive effects of split application in wheat on grain protein content (Ma et al. , Zebarth et al. ), but again without an increase in total grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, characterized by more continental conditions, are reported positive effects of split application in wheat on grain protein content (Ma et al. , Zebarth et al. ), but again without an increase in total grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…The N rate was doubled and the row width was reduced to half compared with CCM, as other research had shown potential response to these treatments (Caldwell and Starrat, 1987;Leibovitch et al 1992;Ma et al 1992 (Grant et al 1985;Rouke 1985;Caldwell and Starrat 1987) (Ma et al 1992) …”
Section: Methodsmentioning
confidence: 99%
“…An increased spike number can result in improved yields even in the absence of lodging (Hill et al 1982). However, ethephon often decreases grain number per spike, and/or the lOOOgrain weight (Moes and Stobbe 1991c;Ma et al 1992). The various responses to ethephon may be due to genotypic sensitivities (Caldwell et al 1988), environmental conditions (Wiersma et al 1986) or both (Caldwell et al 1988).…”
Section: Plant Lodging and Growth Regulatorsmentioning
confidence: 96%